2017
DOI: 10.1039/c6ra27588e
|View full text |Cite|
|
Sign up to set email alerts
|

Advanced anti-corrosion coatings prepared from α-zirconium phosphate/polyurethane nanocomposites

Abstract: This paper presents the first successful application of α-zirconium phosphate/polyurethane (ZrP/PU) nanocomposites for corrosion protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 49 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…White et al reported the influence of oligo-ether-amine (M-600 and M-1000) as surface modifiers on the rheology of epoxy/ZrP suspensions 17 . ZrP nanoplatelets were organically modified with oligo-ether-amine M-1000 in order to obtain α-zirconium phosphate/polyurethane (ZrP/PU) nanocomposites for corrosion protection 18 . kłapyta et al 19 inserted monoamines (Jeffamines M-600, M-1000 and M-2005) into a synthetic Li-fluorotaeniolite (Li-TN).…”
Section: Introductionmentioning
confidence: 99%
“…White et al reported the influence of oligo-ether-amine (M-600 and M-1000) as surface modifiers on the rheology of epoxy/ZrP suspensions 17 . ZrP nanoplatelets were organically modified with oligo-ether-amine M-1000 in order to obtain α-zirconium phosphate/polyurethane (ZrP/PU) nanocomposites for corrosion protection 18 . kłapyta et al 19 inserted monoamines (Jeffamines M-600, M-1000 and M-2005) into a synthetic Li-fluorotaeniolite (Li-TN).…”
Section: Introductionmentioning
confidence: 99%
“…Zirconium phosphate (ZrP) is an inorganic compound that presents interest due to its specific properties: biocompatibility [55,56], thermal stability, ion-exchange ability [57]. These characteristics make possible the utilization of ZrP in catalysis [58], drug-delivery [56], photochemistry [59], anti-corrosion protection [60]. From morphological point of view, ZrP can be found in both amorphous and crystalline form.…”
Section: Inorganic-based Flame Retardantsmentioning
confidence: 99%
“…Therefore, it is reasonable to assume that increasing the difficulty of the diffusion pathway will effectively prevent H 2 O and O 2 from accessing the substrate surface, leading to good anticorrosion properties of the coating. Recently, many studies have shown that nanofiller can effectively enhance the barrier properties of various polymers [14,[43][44][45][46]. This is because their morphologies have high aspect ratios that lengthen the diffusion pathways for moisture or oxygen, leading to improved barrier properties [47,48].…”
Section: Barrier Properties Of Pi Nanocomposite Filmsmentioning
confidence: 99%
“…The potentiodynamic polarization curves for the PI Figure 9. WVTR values of PI and PI nanocomposite films, along with the values for other polymeric nanocomposites from literature [14,[43][44][45][46]. Table 1.…”
Section: Barrier Properties Of Pi Nanocomposite Filmsmentioning
confidence: 99%